Kinerja Keberlanjutan Perusahaan dan Kinerja Keuangan: Dampak Pengunggkapan Environmental, Social and Governance (ESG) Dalam Mempengaruhi Leverage Pada Perusahaan Sektor Transportasi dan Logistik Tahun 2021-2023 - Brilliant, Aulia Beatrice; Prastio, Ridho; Wijaya Z, Rico; Malinda, Istiqomah (Magister Ilmu Akuntansi Universitas Jambi, 2024)
This study aims to analyze corporate sustainability performance and financial performance, focusing on the impact of Environmental, Social, and Governance (ESG) disclosure on leverage in the transportation and logistics sector during the 2021-2023 period. The method used in this research is Structural Equation Modeling-Partial Least Squares (SEM-PLS) with the assistance of WarpPLS software. The data analyzed were obtained from sustainability reports and annual reports of companies listed on the Indonesia Stock Exchange (IDX). The findings indicate that environmental disclosure does not have a significant effect on financial performance measured by leverage. On the contrary, social disclosure has a significant negative impact on financial performance, while governance disclosure has a significant positive effect on financial performance. These findings provide valuable insights for companies in managing ESG disclosures to enhance financial performance and contribute to the literature on the relationship between sustainability and financial performance in the transportation and logistics sector.